CoREST3 exhibits isoform specific expression in Alzheimer’s disease and regulation of HDAC2 - Maksour, Simon; Anastacio, Helena Targa Dias; Lum, Jeremy S.; Walpole, Samara; Newell, Kelly A.; Turner, Calista; Kaban, Adile; Balez, Rachelle; Lim, Julia; Sutherland, Greg T.; Ooi, Lezanne; Dottori, Mirella (BMC biology, 2025)
The epigenetic regulator, histone deacetylase 2 (HDAC2), is dysregulated in Alzheimer's disease (AD), resulting in disruption to neuronal dynamics, memory and cognition. The transcriptional repressor, REST corepressor 3 (CoREST3) has a potential binding site upstream of Hdac2 and therefore we hypothesised CoREST3 would directly regulate HDAC2 and that CoREST3 expression would be altered in the AD brain. CoREST3 exhibited three distinct bands at ~ 70 kDa (band I), ~ 60 kDa (band II) and ~ 55 kDa (band III), which were consistent with CoREST3, as shRNA mediated knockdown reduced levels of all three bands. CoREST3 protein levels (band II) in AD post mortem brain tissue were significantly decreased in the superior temporal gyrus (STG), inferior temporal gyrus (ITG) and precuneus (PRE), whereas CoREST3 Band III was significantly increased in the PRE and primary visual cortex (PVC). Additionally, HDAC2 was significantly decreased by > 50% in the STG, PRE and PVC. CoREST3 bound upstream of the transcription start site of HDAC2 in induced pluripotent stem cell (iPSC)-derived cortical neurons, and gene knockdown of CoREST3 resulted in a significant increase in HDAC2 expression (p < 0.01). Through the overexpression of each of the six CoREST3 isoforms we demonstrated that Band I represents isoform A and isoform E, Band II is likely a combination of isoform B and isoform C and Band III is isoform D and isoform F. The overexpression of CoREST3 isoform A (RCOR3-variant 1 led to a significant twofold increase in HDAC2 protein levels in cortical neurons (p < 0.05), conversely CoREST3 isoform F overexpression resulted in the opposite effect, reducing HDAC2 levels by 48% (p < 0.05). Together these data suggest that CoREST3 plays an isoform specific and direct role in repressing HDAC2, with dysregulated CoREST3 expression in AD possibly contributing to altered HDAC2 levels involved in AD pathogenesis.